A Quantitative Approach to the Impact of Physical Injuries on Athlete Performance - Gao, Qiang (Pacific International Journal, 2025)
This study investigates the impact of physical injuries on the athletic performance of student-athletes at Harbin Sport University. A total of 60 student-athletes were assessed for endurance, strength, and agility through standardized physical tests. The results showed that injured athletes performed significantly worse than non-injured athletes, with a 7.7% decrease in endurance (12-minute run test), a 13.6% reduction in strength (max bench press), and a 6.5% slower time in the agility (shuttle run) test. These findings indicate that physical injuries lead to measurable declines in key performance metrics, which can hinder an athlete's overall athleticism. The study emphasizes the importance of injury prevention, rehabilitation, and psychological support in mitigating the effects of injuries on performance. This research contributes to the understanding of how injuries impact athletic performance and provides insights for improving injury management strategies in sports training.